Resource allocation schemes for wireless asynchronous transfer mode (ATM) network - Alwi, Mohd. Fadel (2004)
With the ever increasing demand for easy portability and mobility of devices supporting diverse mobile multimedia applications, the need for the adaptation of broadband infrastructure to wireless scenario. However, the cost to set up broadband multimedia is very high but ATM network is cheaper. The mobile multimedia networks like the wireless ATM are faced with challenges relating to user mobility management and channel access. In WATM, traffic control is essential in order to protect the network from congestion and to achieve realistic network efficiency. The main objective is designed the resource allocation scheme that can give high (QoS) performance in terms of probability of call lost and handover call. It means performance in terms of probability of new call, handover call dropping for real time connections and the probability of overload for non-real time. All of these will be done in mathematical analysis using Matlab and simulations using COMNET III. The design started with scheme call With Reserved Channel (WRC), which has reserved channels for handover calls. The reserved channel will be getting the good performance in term of QoS. However, this scheme cannot be support for the new incoming calls. Hence, to improve it, the With Queuing and Reserved Channels (WQRC) will be design to handle that problem. This scheme allows queuing of new incoming calls and reserved channels for handover calls. Using WQRC, low probability of handover dropping was maintained and the new call blocking probability was eliminated. The network will be getting the higher link utilization and increase the performance and reliability of the network.